Heat Transfer Performance of Quaternary Molten Nitrate Salt Mixture for Heat Transfer Application - Tukimon, Mohd Faizal; Wan Muhammad, Wan Nur Azrina; Mohamad, Md. Nor Anuar; Yusof, Farazila (Journal of Science and Technology, 2017)
Previous, study has shown that synthetic oil and water are the best medium that can act as heat transfer fluid in heat transfer application. However, in the context of transferring energy, these medium are insufficient for operating at high temperature range due to its characteristic such as low melting point. The use of high temperature molten salt mixture in various industries has resulting big changes in transferring of heat energy. It is proven that the molten salt mixture can carry more heat from one place to another. This study shows the effect of quaternary molten salts mixture consisting of four different salts which are Sodium Nitrate, (NaNO3), Potassium Nitrate, (KNO3), Lithium Nitrate, (LiNO3), and Calcium Nitrate, (Ca(NO3)2) that can enhance the heat transfer rate in heat transfer application. New line of quaternary nitrate salt mixtures (NaNO3 - KNO3- LiNO3 – Ca(NO3)2) were prepared through mixing process. Those mixtures were then heated inside the box furnace at 150oC for four hours and rose up the temperature to 400oC for eight hours to homogenize the mixtures. The temperature was then dropped for several hours until it reaches 115oC before removing the mixture from the furnace. After that, the quaternary molten salt has been placed inside the boiler for heat transfer performance test. The quaternary molten salt was heated inside the boiler and transferred the heat to the working fluid through the copper coil. The inlet and outlet temperatures were recorded by reading the measuring devices that installed at the inlet and outlet of the boiler. At the boiler temperature of 200oC, it is shown at time of 25 minutes, sample 5 with composition of 10wt% NaNO3, 60wt% KNO3, 10wt% LiNO3 and 20wt% Ca(NO3)2 gives the highest value of heat transfer rate which was 2.65kW, meanwhile at boiler temperature of 100oC, sample 2 with composition of 22wt%NaNO3, 40wt%KNO3, 23wt%LiNO3 and 15wt%Ca(NO3)2 gives the lowest value of heat transfer which was 0.37kW. In the nut shell, by replacing the previous heat transfer fluid to quaternary molten salt mixture can increase the heat transfer rate in heat transfer application.